2020
DOI: 10.1515/revneuro-2020-0066
|View full text |Cite
|
Sign up to set email alerts
|

COVID–19 infection and stroke risk

Abstract: Coronavirus disease 2019 (COVID-19), due to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), emerged in Wuhan city, China in December 2019 and rapidly spread to other countries. The most common reported symptoms are fever, dry cough, myalgia and fatigue, headache, anorexia, and breathlessness. Anosmia and dysgeusia as well as gastrointestinal symptoms including nausea and diarrhea are other notable symptoms. This virus also can exhibit neurotropic properties and may also cause neurological dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 127 publications
(146 reference statements)
2
4
0
Order By: Relevance
“…This would result in poor stroke treatment in rural areas, where lives are over 60% of population [17]. Furthermore, we noticed that in overall China, the mortality of stroke surged in 2021, which is consistent with the previous studies that COVID-19 is positively associated with stroke [18,19]. However, during 2020 and 2021, when COVID-19 officially impacted the world, the mortality of stroke in Chongqing slightly increased in 2020 and decreased in 2021, manifesting a minuscule effect due to COVID-19, although there were studies that demonstrated the baleful effects of COVID-19 to stroke.…”
Section: Discussionsupporting
confidence: 90%
“…This would result in poor stroke treatment in rural areas, where lives are over 60% of population [17]. Furthermore, we noticed that in overall China, the mortality of stroke surged in 2021, which is consistent with the previous studies that COVID-19 is positively associated with stroke [18,19]. However, during 2020 and 2021, when COVID-19 officially impacted the world, the mortality of stroke in Chongqing slightly increased in 2020 and decreased in 2021, manifesting a minuscule effect due to COVID-19, although there were studies that demonstrated the baleful effects of COVID-19 to stroke.…”
Section: Discussionsupporting
confidence: 90%
“…3 According to the TOAST classification, this case was classified as a "stroke of unknown cause". Endothelial damage, hypercoagulability, viral myocarditis and hypoxic damage have been proposed as the pathogenesis of COVID-19-related stroke, 4 and in the present case, hypercoagulability was one of the causes of the stroke. In a multivariate analysis controlling for race/ethnicity, COVID-19 infection was significantly and independently associated with large vessel occlusive stroke, with an odds ratio of 2.4.…”
supporting
confidence: 49%
“…Brain fogging or confusion was reported by 9.95% (43), vertigo-like symptoms by 3.47% (15), tingling of the extremity with injection site by sensation in the ears reported by 2.31% (10), ear pain by 1.62% ( 7), blurred vision by 0.93% (4), flashing lights by 0.69% (3), changes in hearing by 0.46% (2), double vision by 0.23% (1), nose bleed by 0.23% (1), bleeding gums by 0.23% (1), and hoarseness by 0.23% (1) of the recipients (432).…”
Section: Neurological Symptomsmentioning
confidence: 99%
“…2 Common symptoms in hospitalized patients with coronavirus disease 2019 (COVID- 19) infection include fever, dry cough, shortness of breath, fatigue, myalgia, nausea, vomiting or diarrhea, headache, weakness, anosmia, ageusia, and rhinorrhea. 3 Common complications [4][5][6][7][8][9][10] with COVID-19 infection include pneumonia, acute respiratory distress syndrome, acute liver failure, cardiac abnormalities with troponin elevation, acute heart failure dysrhythmias, myocarditis, prothrombotic coagulopathy resulting in venous and arterial thromboembolic events, acute renal failure, neurologic manifestations, including impaired consciousness and acute cerebrovascular disease such as stroke, and shock. The overwhelming systemic inflammation and multiorgan failure with high mortality is secondary to "cytokine storm syndrome" (pediatric inflammatory multisystem syndrome in children, which is an immune deregulation characterized by perpetuated activation of lymphocytes and macrophages, resulting in secretion of large quantities of cytokines).…”
Section: Introductionmentioning
confidence: 99%